Analysis Quality of Financial Reporting, Free Cash Flow, Asset Tangibility, and Liquidity of Investment Efficiency with in Moderation to Debt Maturity - Dinda Ayu Septiana; Harjum Muharam; Wisnu Mawardi (Diponegoro Journal of Economics, 2020)
This study aims to analyze the role of free cash flow, asset tangibility, liquidity, and the quality of financial reporting which is moderated by debt maturity in investment efficiency. This study takes State-Owned Enterprises companies listed on the Indonesia Stock Exchange from 2011 to 2017 as a population. The purposive sampling method is used as a sampling in research. The number of companies that can meet the criteria is 17 companies. This study uses data from the company's annual financial statements listed on the Stock Exchange, which consists of total investment, free cash flow, asset tangibility, liquidity, and debt maturity. There are five hypotheses in this study, and analyzed using multiple regression with SPSS tools. The results of this study indicate that the quality of financial reporting has a positive and significant effect on investment efficiency. In addition, the quality of financial reporting moderated by debt maturity has a positive and significant effect on investment efficiency. For free cash flow, asset tangibility, and liquidity do not have an effect on investment efficiency.